Systematic Literature Review : Implementasi Pendekatan PMRI terhadap Kemampuan Pemecahan Masalah Matematika - Musdalipa; Maria Luthfiana; Yufitri Yanto (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
This study aims to analyze the implementation of the Indonesian Realistic Mathematics Education (PMRI) approach to mathematical problem-solving skills based on the results of previous studies, and to identify supporting and inhibiting factors for its success. The method used is a Systematic Literature Review (SLR) with the Zawacki-Richter procedure, which includes the stages of research questions, selection criteria, search strategies, study selection, quality assessment, and synthesis of results. The search for this article was conducted through Google Scholar, SINTA, and Garuda using keywords related to PMRI and mathematical problem-solving skills, with the period 2020-2026. Of the 67 identified articles, 17 articles met the inclusion criteria and were analyzed systematically. The results show that PMRI can be implemented through various forms of contextual learning such as local culture, traditional games, LKPD, e-LKPD, and interactive media. Supporting factors for the success of PMRI include the use of relevant contexts, valid and practical learning tools, and student activeness. Inhibiting factors are abstract materials, conventional learning, and limited learning tools.